Design of laser melting of tool steel for surface integrity enhancement - Fazliana, Fauzun; S. N., Aqida; Izwan, Ismail (Malaysian Tribology Society (MYTRIBOS), 2019)
In this study, laser surface modification hasbeen conducted on AISI H13 tool steel for enhance surface properties. A maximum 300 W high power Nd:YAG laser system with pulse mode was used to modify both materials sample surface. Laser processing was conducted using a 33full factorial design. Three controlled parameters were laser peak power, pulse repetitive frequency (PRF)and scanning speed. The modified surface was characterized for metallographic study, surface morphology and hardness properties. The results showedthat finer grain formation occurred at laser modified layer. Grain size decreased along the cross-section of the melted pool, which consequently increased the hardness due to grain refinement. The overlapincreased significantly with decreasing laser scanning speed which affected samplesurface integrity. Low surface roughness obtained at the highest scanningspeed, low peak power and PRF. Process optimization was carried out for maximum surface hardness and laser modified depth, and minimum surface roughness. These findings indicate potential application of tool steel for thermal wearresistant applications through laser surface modification.